A symbolic decision procedure for relations arising among Taylor coefficients of classical Jacobi theta functions. (September 2017) - Ye, Liangjie
Abstract: The class of objects we consider are algebraic relations between the four kinds of classical Jacobi theta functions θ j ( z | τ ), j = 1, …, 4, and their derivatives. We present an algorithm to prove such relations automatically where the function argument z is zero, but where the parameter τ in the upper half complex plane is arbitrary.